GEOLOGY, AGE AND TECTONIC EVOLUTION OF THE SIERRA MAESTRA MOUNTAINS, SOUTHERN CUBA - Rojas-Agramonte Y.; Neubauer F.; Hejl E.; Handler R.; Bojar A.V.; García-Delgado D.E. (My University, 2006)
We summarize the available geological information on the Sierra Maestra Mountains in southeastern Cuba and report new zircon fission track and biotite Ar-Ar ages for this region. Two different and genetically unrelated volcanic arc sequences occur in the Sierra Maestra, one Cretaceous in age (pre-Maastrichtian) and restricted to a few outcrops on the southern coast, and the other Palaeogene in age, forming the main expression of the mountain range. These two sequences are overlain by middle to late Eocene siliciclastic, carbonatic and terrigenous rocks as well as by late Miocene to Quaternary deposits exposed on the southern flank of the mountain range. These rocks are britle deformed and contain extension gashes filled with calcite and karst material. The Palaeogene volcanic arc successions were intruded by calc-alkaline, low-to medium-K tonalites and trondhjemites during the final stages of subduction and subsequent collision of the Caribbean oceanic plate with the North American continental plate. U-Pb SHRIMP single zircon dating of five granitoid plutons yielded 206Pb/238U emplacement ages between 60.5 ± 2.2 and 48.3 ± 0.5 Ma. These granitoids were emplaced at pressures ranging from 1.8 to 3.0 kbar, corresponding to depths of ca. 4.5-8 km. 40Ar/39Ar dating of two biotite concentrates yielded ages of 50 ± 2 and 54 ± 4 Ma, indicating cooling through ca. 300 °C. Zircon and apatite fission track ages range from 32 ± 3 to 46 ± 4 Ma and 31 ± 10 to 44 ± 13 Ma, respectively, and date cooling through 250 ± 50 °C and 110 ± 20 °C. The granitoids are the result of subduction-related magmatism and have geochemical characteristics similar to those of magmas from intra-oceanic island-arcs such as the Izu Bonin-Mariana arc and the New Britain island arc. Major and trace element patterns suggest evolution of these rocks from a single. © UB-ICTJA.
Keywords: CALC-ALKALINE GRANITOIDS; CUBA; GEOCHRONOLOGY; PALAEOSTRESS ANALYSIS; SUBDUCTION MAGMATISM; TRANSFORM FAULT; WRENCH CORRIDOR; Quaternary; Miocene; Eocene; Maastrichtian; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Mesozoic::Cretaceous::Upper::Maastrichtian; Мезозой::Меловая::Верхний::Маастрихтский